Evaluation of the clinico-laboratory manifestations of newly diagnosed multiple myeloma - Angela Ogechukwu Ugwu (International Journal of Medicine and Health Development, 2022)
Background: Multiple myeloma (MM) is a very common hematological malignancy and constitutes about 10% of hematological malignancies. Laboratory investigations including haematological, biochemical, and molecular studies play an important role in the diagnosis, monitoring of response, and relapse in patients with MM. Objectives: The objectives of this article were to assess the initial clinical features, hematological profile, and biochemical parameters of newly diagnosed patients with MM. Materials and Methods: This was a retrospective study of MM patients seen from February 2010 to January 2020 at a tertiary hospital in Nigeria. A total of 51 patients’ case notes were retrieved from the Medical Records Department of the hospital. The socio-demographic data were collected using a Microsoft Excel Sheet. Data on age, sex, hematological parameters, presence of bone lesions (fractures, and osteolytic findings from radiographs), and biochemical parameters were extracted and analyzed. Results: The median age was 60.5 years, and the mean age was 59.6 ± 9.3 with a range of 35–89 years and a male-to-female ratio of 1.7:1. Only 1 (2.0%) patient was aged below 40 years, and the rest 50 (98.0%) were above 40 years of age. The 61–70 age group had the highest number of cases, 31 (60.8%). The mean hemoglobin, white cell count, and platelet count were 7.96 ± 2.2; 6.76 ± 0.6; and 213.50 ± 98 respectively. Serum protein was >80 g/L in 33 (64.7%) and <80 g/L in 18 (35.3%) patients. Two-thirds of the patients, 34 (66.7%) had albumin level <35 g/L. The mean albumin and globulin levels were 36.2 ± 10.9 and 59.2 ± 1.9 respectively, giving an albumin–globulin ratio (AGR) of 0.611. The mean calcium level was 2.6 ± 0.29 mmol/L. The overall mean urea and creatinine levels were 8.02 ± 3.2 (mmol/L) and 169.5 ± 89.4 (μmol/L), respectively. The most common clinical presentations were weakness, pallor, and bone pains with a proportion of 49 (96.1%), 47 (92.2%), and 45 (88.3%), respectively. Conclusion: The physicians should be alerted on the possibility of MM when an elderly patient presents with weakness and bone pains. The AGR is commonly low, connoting a poor prognosis.